2020
DOI: 10.1177/1740774520931864
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Education, and Exercise for age-related cognitive decline: Study protocol, pilot study results, and description of the baseline sample

Abstract: Background/Aims Age-related cognitive decline is a pervasive problem in our aging population. To date, no pharmacological treatments to halt or reverse cognitive decline are available. Behavioral interventions, such as physical exercise and Mindfulness-Based Stress Reduction, may reduce or reverse cognitive decline, but rigorously designed randomized controlled trials are needed to test the efficacy of such interventions. Methods Here, we describe the design of the Mindfulness, Education, and Exercise study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 84 publications
4
21
0
Order By: Relevance
“…4 Future studies should consider a longer duration of the AT and more accessible forms of aerobic exercise (e.g., neighborhood walking), especially considering recent findings that light aerobic exercise increases brain volume. 26 To our knowledge, there is only 1 (ongoing) study exploring effects of MT and AT on cognitive function, 27 and thus, the literature does not offer many insights. A 2 × 2 RCT of cognitive training and aerobic activity found no differences between groups, but used a very active control condition, 11 while a small RCT suggested that combined aerobic and cognitive training could lead to larger effects than either intervention alone.…”
Section: Discussionmentioning
confidence: 99%
“…4 Future studies should consider a longer duration of the AT and more accessible forms of aerobic exercise (e.g., neighborhood walking), especially considering recent findings that light aerobic exercise increases brain volume. 26 To our knowledge, there is only 1 (ongoing) study exploring effects of MT and AT on cognitive function, 27 and thus, the literature does not offer many insights. A 2 × 2 RCT of cognitive training and aerobic activity found no differences between groups, but used a very active control condition, 11 while a small RCT suggested that combined aerobic and cognitive training could lead to larger effects than either intervention alone.…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI data were processed following methods described by Raut et al 41 . Briefly, the preprocessing reduced slice and time dependent intensity artifacts and noise, standardized the whole brain intensity to mode value of 1000, corrected for within‐run head movement, and registered the data to a standardized space using an Atlas generated from 208 subjects from the MEDEX study 39 which used an identical protocol on the same scanner model. Multi‐echo data were analyzed by least squares fitting of the theoretical model defined in equation 1 in Poser et al 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Functional MRI data were processed following methods described by Raut et al 41 Briefly, the preprocessing reduced slice and time dependent intensity artifacts and noise, standardized the whole brain intensity to mode value of 1000, corrected for within-run head movement, and registered the data to a standardized space using an Atlas generated from 208 subjects from the MEDEX study 39 which used an identical protocol on the same scanner model. Multi-echo data were analyzed by least squares fitting of the theoretical model defined in equation 1 in Poser et al 42 The fitted data then were converted to synthetic T2*-weighted images evaluated at TE = 30 ms. Nuisance regression was performed using white matter and ventricle segmentation generated from FreeSurfer acquisition, the mean video BOLD response averaged over all participants was subtracted from each subject time series.…”
Section: Image Data Analysismentioning
confidence: 99%
“…Ninety-five community-dwelling older aged adults (67–87 years) were included in the StayWELL study. All had previously participated in the Mindfulness, Education, and Exercise (MEDEX) study ( 27 ) and were concurrently enrolled in an extension trial. The MEDEX study was a now-concluded 18-month randomized controlled trial to assess the effects of in-person interventions, which included three active treatments, i.e.…”
Section: Methodsmentioning
confidence: 99%